Factors Associated With Administration of Antiplatelet Therapy on The NIHSS Score in Acute Ischemic Stroke - Chrisstawati, Eddy Ratnaningsih; Wijayanti, M.I. Ekatrina; Wibowo, Tandean Arif (Jurnal Riset Kesehatan, 2023)
Stroke is the highest cause of death in the world. Antiplatelet therapy is one of the important therapies in acute ischemic stroke patients. Antiplatelet works by inhibiting platelet aggregation. In the implementation of antiplatelet therapy administration, it was found that (26.9%) administration was done more than 6 hours since the doctor's program. To find out quantitative outcomes in stroke patients, the NIHSS examination was carried out. To determine the factors related to antiplatelet administration to the NIHSS score in acute ischemic stroke patients at "X" Hospital Yogyakarta. This study uses the correlation method with a retrospective approach. Documentation studies (secondary data) were used in collecting data. The number of samples was 64 respondents from a total population of 465 patients with an ischemic stroke diagnosis. The probability sampling technique was used with a simple random sampling technique in taking the sample. Of the total sample of 82 respondents, 64 samples passed for analysis. Non-parametric Spearman test was used for analysis. These results suggest that within the scope of this study, the timing, type, and dosage of antiplatelet therapy did not show a significant impact on the severity of stroke symptoms as measured by NIHSS scores among the patients studied at "X" Hospital in Yogyakarta.